EFFECT OF CONSTRAINING AND STIMULATING FACTORS ON THE SUSTAINABLE DEVELOPMENT OF THE INFORMATION SPHERE OF UKRAINE - О.В. Мельников; Я.В. Котляревський; С.І. Князєв; А.М. Штангрет (Економіка та право, 2024)
The article is focused on modern aspects of the development of the information sphere of Ukraine taking into consideration influence of constraining and stimulating factors. Thus, authors investigated the essence of those factors, some actual trends of it’s recent definition and applied socio-economic outcomes for state regulation. Consequently, a research methodology model was elaborated grounded on matrix form assessment of expert qualitative considerations towards analyzing finite set of factors.